Geothermal power plants of Iceland: a technical survey of existing and planned installations - DiPippo, R. (Southeastern Massachusetts Univ., North Dartmouth (USA), 1978)
The technical features of the geothermal electric power plants of Iceland are described. Some description is given of the geology of the geothermal regions, and recent volcanic eruptions are discussed relative to their impact on the geothermal plant sites. The 3 MW, single-flash plant at Namafjall, the 60 MW, double-flash plant at Krafla, and the 1 MW unit at Grindavik are included. Information is given on well arrangements, casing programs, energy conversion systems, capital investments, and operating experiences, where such information is available.